Tumor Microenvironment Responsive Pepper Mild Mottle Virus-Based Nanotubes for Targeted Delivery and Controlled Release of Paclitaxel - Peng, Jiejun; Yin, Yueyan; Liang, Hongze; Lu, Yuwen; Zheng, Hongying; Wu, Guanwei; Rao, Shaofei; Chen, Jianping; Yan, Fei; Hu, Jingbo (Frontiers in Bioengineering and Biotechnology, 2021)
Plant virus nanoparticles (PVNPs) have been widely used for drug delivery, antibody development and medical imaging because of their good biodegradation and biocompatibility. Particles of pepper mild mottle virus (PMMoV) are elongated and may be useful as drug carriers because their shape favours long circulation, preferential distribution and increased cellular uptake. Moreover, its effective degradation in an acidic microenvironment enables a pH- responsive release of the encapsulated drug. In this study, genetic engineering techniques were used to form rod-shaped structures of nanoparticles (PMMoV) and folated-modified PMMoV nanotubes were prepared by polyethylene glycol (PEG) to provide targeted delivery of paclitaxel (PTX). FA@PMMoV@PTX nanotubes were designed to selectively target tumor cells and to release the encapsulated PTX in response to pH. Efficient cell uptake of FA@PMMoV@PTX nanotubes was observed when incubated with tumor cells, and FA@PMMoV@PTX nanotubes had superior cytotoxicity to free PTX, as reflected by cell survival and apoptosis. This system is a strong candidate for use in developing improved strategies for targeted treatment of tumors.